2016
DOI: 10.1016/j.berh.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cultural influences on back pain and back pain research

Abstract: Low back pain is highly prevalent and places a considerable burden on individuals, their families and communities. This back pain burden is unequally distributed around the world and within populations. Clinicians and researchers addressing back pain should be aware of the cultural, social and political context of back pain patients and how this context can influence pain perception, disability and health care use. Culture, which influences the beliefs and behaviour of individuals within a social group, could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 76 publications
4
24
0
2
Order By: Relevance
“…The different belief system of LBP population in China found in our study, supports research that suggests that cultural factors in uence pain-related factors (29,30,(58)(59)(60). For example, in contrast with the overwhelming LBP medical care in the West (13,21,28), a Nepalese study showed that people who suffered from LBP continued with their daily activities without seeking medical help as they consider LBP to be a normal aging process (58).…”
Section: Discussionsupporting
confidence: 79%
“…The different belief system of LBP population in China found in our study, supports research that suggests that cultural factors in uence pain-related factors (29,30,(58)(59)(60). For example, in contrast with the overwhelming LBP medical care in the West (13,21,28), a Nepalese study showed that people who suffered from LBP continued with their daily activities without seeking medical help as they consider LBP to be a normal aging process (58).…”
Section: Discussionsupporting
confidence: 79%
“…We have also attempted to address any potential issues by not overstating the comparisons between the ndings of the two studies. The different belief system of LBP population in China found in our study, supports research that suggests that cultural factors in uence pain-related factors (19,33,34,61,63). For example, in contrast with the overwhelming LBP medical care in the West (14,25,32), a Nepalese study showed that people who suffered from LBP continued with their daily activities without seeking medical help as they consider LBP to be a normal aging process (61).…”
Section: Discussionsupporting
confidence: 78%
“…There is now considerable research, predominantly conducted in the West, that suggests that attributing LBP to an anatomical basis has an important in uence on patients' beliefs. These pain related beliefs are considered to be formed by an individual's past experience of pain and healthcare (18) as well as cultural in uences (19). There is also a large body of research which suggests that there are psychological effects of such biological pain beliefs such as fear avoidance, low self-e cacy and pain catastrophizing beliefs which are related to delayed recovery, poor clinical outcome and chronicity of LBP (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The cultural, social, and political environment of back pain can influence the perception of pain, the disability created, and the use of health care [ 4 ]. High-quality economic appraisals of looking at surgery when compared to conservative care (with the use of different treatment options) are needed in chronic low back pain (CLBP) patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%